From the editors - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
From the Editors MULTIWORD PATTERNS: CONSIDERING PHRASAL VERBS AND THEIR UNDERLYING SEMANTIC SYSTEMS (II) This is the second volume in Language Value that is thoroughly devoted to the issue of Verb Particle Combinations (VPCs) also known and analysed under different linguistic trends and terms as phrasal/prepositional verbs, compound verbs, discontinuous verbs or multiword verbs, among others. For the sake of simplicity we will use the term verb particle combinations (VPCs) throughout this editorial.